Odpowiedzi

2010-03-09T22:05:52+01:00
1) √1/27 * √3-(-1/2)⁰=1/3√3*√3-1=√3/3√3-1=1/2√3-1
2)((√3)³)² - ((-√3)²)³=(√3)²)³-(-√3)²)³=3³-3³=0
3)√3,5 * 2√7/8 - 3³√0,02/∛0,16=2√35/10*7/8-3∛0,02/∛0,02*8=2√245/80-3∛0,02/2∛0,02=2√49/16-∛0,02=2*7/4-∛0,02=14/4-∛0,02
4)√0,8÷√0,008/(-0,1)² + ∛0,1/∛2,7=√4*0,2÷√0,2*0,04/0,01+∛0,1/∛0,1*27=
2√0,2÷0,2√0,2/0,01+∛0,1/3∛0,1=10/0,01+1/2∛0,1=100+1/2∛0,1
Najlepsza Odpowiedź!
2010-03-09T22:07:34+01:00
1) √1/27 * √3-(-1/2)⁰= ¹/₃ * √3 - 1 = ¹/₃√3 - 1
2)((√3)³)² - ((-√3)²)³= 81 - 27 = 54
3)√3,5 * 2√7/8 - 3³√0,02/∛0,16 = 2,5 - 3³√0,125 = 2,5 - 3 * 0,5 = 1
4)√0,8÷√0,008/(-0,1)² + ∛0,1/∛2,7= √100/0,01 + ³√¹/₂₇ = 1000 + ¹/₃ = 1000¹/₃
1 1 1